PERSEPSI MASYARAKAT MENGENAI PENGAPLIKASIAN 5M PASCA VAKSINASI SEBAGAI PENCEGAHAN COVID-19 DI PLUMBON KABUPATEN CIREBON - Hafidz Al Qodri; Fitri Alfiani; Asep Novi Taufiq Firdaus (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2022)
The government's program in breaking the chain of spread of Covid-19, namely the implementation of the post-vaccination 5M policy (Washing hands, maintaining distance, wearing masks, avoiding crowds, and reducing mobility) is a follow-up effort from the previous movement, namely 3M (Washing hands, maintaining distance, and wearing a mask) which is set by the government in order to deal with cases of the spread of Covid-19. One of the factors causing community compliance in implementing 5M post-vaccination is the individual's perception. This study aims to determine the public's perception of the application of post-vaccination 5M as an effort to prevent covid-19 in the Plumbon, Cirebon Regency. The research method used is descriptive qualitative with a phenomenological approach.  The sampling technique used purposive sampling with a total of 8 informants.  Data were collected using interviews, documentation and observation.  Data analysis uses description, reduction, data presentation and conclusion drawing.  The validity of the data using triangulation of sources and methods. The results of the study obtained 5 main themes, namely: public knowledge about the covid-19 virus, public description of the covid-19 vaccination, public perception of the post-vaccination 5M policy, the impact of government policy regarding the post-vaccination 5M movement, public compliance with the implementation of government policies. The conclusion of this study is the perception that emerged in the community after vaccination was that 8 informants assumed that after the vaccine was given, they would be immune from Covid-19 transmission, so many of the informants began to ignore the government's recommendation regarding 5M post-vaccination.